Executive Committee Minutes 2007-05-03 - Academic Senate:::::::::
Collegiate Learning Assessment, Revision of Probation, Disqualification and Progress policy, Discussion of process regarding authorizing a referendum of no confidence in the President now pending before the Senate, Survey of Executive Committee and Senate, Advising Policy